Enhancing organic selenium content and antioxidant activities of soy sauce using nano-selenium during soybean soaking - Chen, Jingru; Feng, Tuo; Wang, Bo; He, Ronghai; Xu, Yanling; Gao, Peipei; Zhang, Zhi-Hong; Zhang, Lei; Fu, Jiangyan; Liu, Zhan; Gao, Xianli (Frontiers in Nutrition, 2022)
Nano-selenium has a greater potential than inorganic selenium in preventing selenium-deficiency diseases due to its higher safety. In this study, spherical nano-selenium particles (53.8 nm) were prepared using sodium selenite, ascorbic acid and chitosan. Selenium-enriched soy sauces were prepared by soaking soybean in nano-selenium and sodium selenite solutions (2–10 mg/L), respectively. Total selenium and organic selenium contents of soy sauces prepared by nano-selenium and sodium selenite were increased by 32–191-fold and 29–173-fold compared to the Control (without selenium), and organic selenium accounted for over 90% of total selenium. Soy sauce prepared using 6 mg/L nano-selenium had the strongest antioxidant activities, which were 9.25–28.02% higher than the Control. Nano-selenium (6 mg/L) markedly improved koji’s enzyme activities (9.76–33.59%), promoting release of total phenolics (27.54%), total flavonoids (27.27%) and formation of free amino acids (16.19%), Maillard reaction products (24.50%), and enhanced antioxidant activities of the selenium-enriched soy sauce.